2009
DOI: 10.1186/1756-9966-28-158
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Twist expression and its association with E-cadherin in esophageal squamous cell carcinoma

Abstract: BackgroundTwist is a basic helix-loop-helix (bHLH) transcriptional factor that has been identified to play an important role in epithelial-mesenchymal transition (EMT)-mediated metastasis through the regulation of E-cadherin expression. However, few authors have examined the expression of Twist and E-cadherin and their prognostic value in patients with esophageal squamous cell carcinoma (ESCC). The purpose of this study is to evaluate the clinical significance of Twist and E-cadherin expression in ESCC.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(70 citation statements)
references
References 23 publications
3
64
0
3
Order By: Relevance
“…Low E-cadherin expression was significantly associated with a high SUVmax in the present study. Previously, it was reported that reduced E-cadherin expression is associated with tumor invasion, metastasis and a poor prognosis for patients with ESCC (24,25). Our results are comparable with those findings.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Low E-cadherin expression was significantly associated with a high SUVmax in the present study. Previously, it was reported that reduced E-cadherin expression is associated with tumor invasion, metastasis and a poor prognosis for patients with ESCC (24,25). Our results are comparable with those findings.…”
Section: Discussionsupporting
confidence: 83%
“…Growth factors, cytokines, extracellular matrix components and transcription factors are involved in EMT induction in epithelial tumor cells (21,22). Results of recent studies (24)(25)(26)(27)(28)(29) suggest that EMT is associated with tumor invasion, metastasis and prognosis in ESCC. However, an association between SUVmax derived from FDG-PET/CT and EMT markers in ESCC remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of E-cadherin expression is a well-documented condition for invasiveness; [14][15][16][17][18][19][20] however, this result is debatable. 3,4 Our work demonstrated that the loss of E-cadherin itself, without a mesenchymal phenotype, may not be associated with invasive behavior, whereas tumors with a mesenchymal phenotype, regardless of E-cadherin expression, showed aggressive behavior in esophageal squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…This TGF-beta is one of the factors that can induce an Epithelial-to-Mesenchymal Transition (EMT) [80] . For different types of tumors it has been demonstrated that an EMT-switch is associated with a worse prognosis as seen in esophageal squamous cell carcinoom [81] , gastric cancer cells [82] bladder cancer [83] non-small cell lung cancer [84] and pancreas ductal adenomacarcinoma [85] . For HCC, this correlation has also been found with an independent effect of Twist and Snail in promoting metastasis of hepatocellular carcinoma [86][87][88][89] .…”
Section: Hepatocarcinogenesis and Tumormicroenviromentmentioning
confidence: 99%